2016
DOI: 10.1038/nm0616-692b
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: ROR-γ drives androgen receptor expression and represents a therapeutic target in castration-resistant prostate cancer

Abstract: In the version of this article initially published online, there were two errors. There was a typographical error in the text, which should have stated that the 'dark current' is an electrochemical gradient required for photon-induced polarization (rather than depolarization, as incorrectly stated). In addition, some funding sources were inadvertently omitted from the Acknowledgments. The errors have been corrected for the print, PDF and HTML versions of this article.Corrigendum: ROR-γ drives androgen receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…IL-23 has been reported to regulate the activation of STAT3/RORγ expression in naive CD4 T cells2628; both STAT3 and RORγ can impact AR signaling in prostate cancer29,30. We therefore evaluated whether IL23 secreted by MDSCs impacted the STAT3/RORγ axis in prostate cancer in a non-cell autonomous manner.…”
Section: Mdscs Activate the Il23/rorγ Pathwaymentioning
confidence: 99%
“…IL-23 has been reported to regulate the activation of STAT3/RORγ expression in naive CD4 T cells2628; both STAT3 and RORγ can impact AR signaling in prostate cancer29,30. We therefore evaluated whether IL23 secreted by MDSCs impacted the STAT3/RORγ axis in prostate cancer in a non-cell autonomous manner.…”
Section: Mdscs Activate the Il23/rorγ Pathwaymentioning
confidence: 99%
“…In castration-resistant prostate cancer (CRPC), RORγ was examined as a therapeutic target due to its overexpression and was found to directly drive androgen receptor (AR) hyperactivity through binding to an exonic RORE and partly through the NR coactivators SRC-1 and -3 ( 35 ). Therefore, inhibition of RORγ may represent a possible treatment option for CRPC.…”
Section: Cancer Relevancementioning
confidence: 99%
“…Some studies suggest that RORα is a tumor suppressor and a potential therapeutic target for BC; and based on the limited researches on RORβ in cancer, RORβ might be a tumor suppressor as well. Others have proposed that activating RORγ may exert antitumor immunity ( 34 ), while RORγ is considered as protumor candidates in prostate cancer and lung cancer ( 4 , 35 ). In this review, we summarize and discuss the structures of RORs and their roles in cancer-related processes, highlighting the potential therapeutic targets for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…2A ). We used XY018, a RORγ-selective antagonist [ 32 ], fatostatin (FS), which directly blocks SREBP2 by preventing its translocation to the Golgi apparatus [ 37 ] and atorvastatin (ATV), a widely used inhibitor of HMGCR to block cholesterol synthesis [ 23 ]. To define the cytotoxic profile and possible treatment side-effects, we used CD34+ cells with high levels of SREBF2 mRNA and CD34- cells with low levels as control cells.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, inhibition of retinoic acid receptor (RAR)-related orphan receptor gamma (RORγ) abolished the entire cholesterol biosynthesis program, circumventing reactivation of metabolism and the feedback loop, as previously shown in studies with triple-negative breast cancer (TNBC) and prostate cancer cells. They have demonstrated that RORγ is an important driver of tumor growth, which could be successfully diminished by newly established RORγ antagonists [ 32 , 33 ]. Importantly, RORγ has two isoforms and while RORγt (isoform 2) is highly expressed in sub-populations of immune cells and plays a critical role in the differentiation of Th17 cells, RORγ (isoform 1) has been shown to play an important role in controlling metabolic pathways [ 33 ].…”
Section: Introductionmentioning
confidence: 99%